Computer Vision and Image Processing 6th International Conference, CVIP 2021, Rupnagar, India, December 3-5, 2021, Revised Selected Papers, Part II - Raman, Balasubramanian; Murala, Subrahmanyam; Chowdhury, Ananda; Dhall, Abhinav; Goyal, Puneet (Cham : Springer International Publishing : Imprint: Springer, 2022)
This two-volume set (CCIS 1567-1568) constitutes the refereed proceedings of the 6h International Conference on Computer Vision and Image Processing, CVIP 2021, held in Rupnagar, India, in December 2021. The 70 full papers and 20 short papers were carefully reviewed and selected from the 260 submissions. The papers present recent research on such topics as biometrics, forensics, content protection, image enhancement/super-resolution/restoration, motion and tracking, image or video retrieval, image, image/video processing for autonomous vehicles, video scene understanding, human-computer interaction, document image analysis, face, iris, emotion, sign language and gesture recognition, 3D image/video processing, action and event detection/recognition, medical image and video analysis, vision-based human GAIT analysis, remote sensing, and more.
Handwritten Text Retrieval from Unlabeled Collections -- Detecting Document Forgery Using Hyperspectral Imaging -- An Hour-glass CNN for Language Identification of Indic Texts in Digital Images -- Single Frame-based Video Dehazing with Adversarial Learning -- Spatio-Temporal Event Segmentation for Wildlife Extended Videos -- Comparative analysis of machine learning and deep learning models for ship classication from satellite images -- Channel Dierence based Regeneration Architecture for Fake Colorized Image Detection -- DenseASPP enriched Residual Network towards visual saliency prediction -- Brain MRI and CT Image Fusion Using Generative Adversarial Network -- MFCA-Net: Multiscale Feature Fusion with Channel-wise Attention Network for Automatic Liver Segmentation from CT Images -- Automatic Double Contact Fault Detection in Outdoor Volleyball Videos -- Classroom Slide Narration System -- Humanoid Robot - Spark -- Attention-Based Deep Autoencoder for Hyperspectral Image Denoising -- Feature Modulating Two-stream Deep Convolutional Neural Network for Glaucoma Detection in Fundus Images -- Retinal Image Quality Assessment using Sharpness and Connected Components -- Multi-frame Motion Saliency Learning for Object Segmentation -- Video Enhancement with Single Frame -- Blind Video Quality Assessment using Fusion of Novel Structural Features and Deep Features -- On-Device Spatial Attention based Sequence Learning Approach for Scene Text Script Identication -- Post-Harvest Handling of Mangoes: An Integrated Solution Using Machine Learning Approach -- Morphological Gradient Analysis and Contour Feature Learning for Locating Text in Natural Scene Images -- Introspecting Local Binary Feature Vectors for Classification of Radiographic Weld Images -- Performance Evaluation of Deep Learning Models for Ship Detection -- COVID-19 Social Distance Surveillance using Deep Learning -- Towards Semi-supervised Tree Canopy Detection and Extraction from UAV Images -- Pose Guided Controllable Gesture to gesture translation -- EDR: Enriched Deep Residual Framework with Image Reconstruction for Medical Image retrieval -- Depth Estimation Using Sparse Depth And Transformer -- Analysis of Loss Functions for Image Reconstruction using Convolutional Autoencoder -- Fuzzy Entropy k-Plane Clustering Method and its Application to Medical Image Segmentation. -- FMD-cGAN: Fast Motion Deblurring using Conditional Generative Adversarial Networks -- Region Extraction Based Approach For Cigarette Usage Classication Using Deep Learning -- Fire Detection Model using Deep Learning Techniques -- Two Novel Methods for Multiple Kinect v2 Sensor Calibration -- Residual Inception Cycle-Consistent Adversarial Networks -- MAG-Net : A memory augmented generative framework for Video anomaly detection using extrapolation -- Hand Gesture Recognition using CBAM-RetinaNet -- Elderly Patient Fall Detection using Video Surveillance -- OGGN: A Novel Generalized Oracle Guided Generative Architecture for Modelling Inverse Function of Articial Neural Networks -- Deep Learning Based DR Medical Image Classication -- Human Action Recognition in Still Images -- Enhancing unsupervised video representation learning by temporal contrastive modelling using 2d CNN -- Deep Two-Stage LiDAR Depth Completion -- 3D Multi-voxel pattern based machine learning for multi-center fMRI data normalization -- EFFICIENT APPROXIMATION OF CURVE-SHAPED OBJECTS IN Z2 BASED ON THE MAXIMUM DIFFERENCE BETWEEN DISCRETE CURVATURE VALUES -- Exploring the role of adversarial attacks in image anti-forensics -- A Novel Articial Intelligence-based Lung Nodule Segmentation and Classication System on CT Scans.
Keywords: Image processing-Digital techniques; Computer vision; Machine learning; Social sciences-Data processing; Education-Data processing; Application software; Database management; Computer Imaging, Vision, Pattern Recognition and Graphics; Machine Learning; Computer Application in Social and Behavioral Sciences; Computers and Education; Computer and Information Systems Applications; Database Management